2011
DOI: 10.1021/jp205529c
|View full text |Cite
|
Sign up to set email alerts
|

Computational High-Frequency Overtone Spectra of the Water–Ammonia Complex

Abstract: We have computed vibrational high-frequency overtone spectra of the water-ammonia complex, H(2)O-NH(3), and its isotopomers. The complex has been modeled as two independently vibrating monomer units. The internal coordinate Hamiltonians for each monomer unit have been constructed using exact gas phase kinetic energy operators. The potential energy and dipole moment surfaces have been calculated with the explicitly correlated coupled cluster method CCSD(T)-F12A and the valence triple-ζ VTZ-F12 basis around the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…28 The torsional coordinate isomerizes the H 2 O· · ·NH 3 complex from the most stable trans-conformation to the cis-conformation (see Figure S3 44 ). Sälli et al 27 showed that the OH b -stretching wavenumber varies by 0.5 cm −1 between the cis-and trans-conformer of the H 2 O· · ·NH 3 complex. Moreover, Lane and Kjaergaard 24 have shown that the barrier between these two conformers is only a few wavenumbers.…”
Section: Definition Of Vibrational Coordinatesmentioning
confidence: 99%
See 4 more Smart Citations
“…28 The torsional coordinate isomerizes the H 2 O· · ·NH 3 complex from the most stable trans-conformation to the cis-conformation (see Figure S3 44 ). Sälli et al 27 showed that the OH b -stretching wavenumber varies by 0.5 cm −1 between the cis-and trans-conformer of the H 2 O· · ·NH 3 complex. Moreover, Lane and Kjaergaard 24 have shown that the barrier between these two conformers is only a few wavenumbers.…”
Section: Definition Of Vibrational Coordinatesmentioning
confidence: 99%
“…For complexes containing H 2 O as the donor unit, the two OH-stretches and the H f OH b bend of the donor unit have been included. 27,29 The Hamiltonian for this three-dimensional system iŝ…”
Section: The Lmpt Modelmentioning
confidence: 99%
See 3 more Smart Citations